A New, Fast and Easy Strategy for One‐pot Synthesis of Full Substituted Cyclopropanes: Direct Transformation of Aldehydes to 3‐Aryl‐1, 1, 2, 2‐tetracyanocyclopropanes. Issue 1 (4th October 2012) - Pesyan, Nader Noroozi; Kimia, Mohammad Ali; Jalilzadeh, Mohammad; Şahin, Ertan
Abstract A new, fast and easy method for one‐pot reaction of aromatic aldehydes and dialdehydes with malononitrile and cyanogen bromide has been developed to afford full substituted 3‐arylcyclopropane‐1, 1, 2, 2‐tetracarbonitriles in excellent yields in very short time (about 5 seconds). The structures elucidations werev characterized by IR, 1H NMR, 13C NMR, mass spectrometry and X‐ray crystallography techniques. For vthese compounds the crystallographic data showed two structures in mirror image in solid case and one distinct structure in solution. The reaction mechanism was discussed.